Adapting to cultural pluralism in urban classrooms - Florence, Namulundah, 1958- (New York, NY : Routledge, 2021)
"This book highlights the need for cultural adaptations in the academic success of inner-city students served by predominantly white and more privileged teachers. Although the discussion centers on inner city minority students in the US, similar concerns extend to underserved students across the globe, whose communities in large part exhibit higher child mortality rates, incarceration rates, and unemployment. Including reflective activities, chapters focus on four elements in the teaching/learning process: school climate; the expectations of teachers in solidarity with administration; teacher interactions with students and parents; and the centrality of reflection to improve practice"--
OCLC-licensed vendor bibliographic record.
Keywords: Culturally relevant pedagogy -- United States; Education, Urban -- United States; Cultural pluralism -- United States; EDUCATION / General; Underserved students